Professional development and efficacy of teaching university professor, University National Hermilio Valdizán - Huánuco 2013 - Portocarrero M., Ewer (2014)
Objective. To determine the degree of relationship between professional development and teacher self-efficacy. Methods. They conducted a correlational study with 125 teachers of the National University Hermilio Valdizan, Huanuco during 2013. We used a form of documentary analysis and self-efficacy scale. For inferential analysis we used the Pearson correlation coefficient. Results. As for the professional development of teachers 78.4% achieved academic master’s degree and 52.0% were exclusive dedication. The 76.0% had high self-efficacy and high frequency of 59.2% the same. They found a significant positive relationship between professional development and teacher self-efficacy (r = 0.64, p ≤ 0.000) and planning dimensions of teaching (r = 0.64, p ≤ 0.000), involvement of students in learning (r = 0.64, p ≤ 0.000), interaction and creation of a positive climate in the classroom (r = 0.63, p ≤ 0.000) and assessment of learning (r = 0.62, p ≤ 0.000). Conclusions. There is relationship between professional development and teacher self-efficacy of university professors from the National University of Huanuco Valdizan Hermilio.